The Influence of Work-Life Balance, Training and Development on Employee Retention: Case Study of Millennial Employees at PT Serdang Multi Sarana - Nainggolan, Natasya Salsabila; Lubis, Fauzi Arif; Nurbaiti, N (Journal of Economics and Management Scienties, 2025)
This study looks at how work-life balance, together with training and development, affect millennial employees' retention at PT Serdang Multi Sarana, a retail company that will have a high turnover rate of 13.89% in 2024. The study used a quantitative method with a causal approach and total sampling methodologies to determine the sample, which consists of 31 employees, all of whom are millennials. A likert scale questionnaire was used to gather data, and PLS-SEM was used for analysis. The findings demonstrated that employee retention was positively and significantly impacted by both work-life balance and training and development, with training and development having a greater impact than work-life balance. These results lend credence to the social exchange theory, which holds that when a company offers millennial workers a healthy work-life balance and sufficient opportunities for self-improvement, they will reciprocate in the form of loyalty. As a result, it can be a tactic used by businesses to lower their still high turnover rate. This study adds to the body of knowledge on human resource management in Indonesia and gives businesses a foundation for creating flexible HR policies that would help them retain millennial workers in the retail industry.